The long-term integration of European refugees: Swedish experiences after the Yugoslav wars - Olof Åslund; Linus Liljeberg; Sara Roman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
We study the short- and long-term economic and social integration of European war refugees. The population under study left former Yugoslavia for Sweden in the early 1990s. In the first years, there were significant human capital investments in language training, adult education, and active labor market programs. The Yugoslav refugees then exhibited a remarkably sharp increase in employment and earnings, possibly helped by improving labor markets and pre-existing contacts in Sweden. Many entered jobs in manufacturing and service industries and remained there to a considerable extent. Among those above 50 at arrival, labor market outcomes were not as good. Despite strong development during the early years, the long-term labor market position of the Yugoslavs is broadly on par with previous cohorts of refugees. Residential segregation first increased and then declined, whereas workplace segregation was most marked among the early entrants.
Keywords: F22; J15; J18; 330; Refugees; migrants; economic and social integration